Makna Simbolik Lompat Batu Nias dalam Perspektif Sastra dan Budaya: Kajian Semiotik Roland Barthes - Sihombing, Anju; Sobirin, Muhammad; Herman, Hidayat (Literasi Bahasa dan Sastra Jurnal, 2025)
This article examined the symbolic meaning of the Nias Stone Jump (Fahombo Batu) within the framework of literary and cultural studies, using Roland Barthes’ semiotic theory (1964) as the main analytical approach. The research problem arises from the phenomenon that the traditional practice of jumping over stone walls in Nias, originally rooted in rituals of maturity, bravery, and social identity, has undergone a shift in meaning due to modernization and tourism commercialization. The study seeks to uncover how these transformations affect the symbolic and narrative layers of the tradition when interpreted as a cultural text. Employing a qualitative descriptive method through semiotic analysis, the research identifies and interprets the denotative, connotative, and mythic levels of meaning embedded in the tradition. Primary data were obtained from field documentation, interviews, and literary sources depicting the cultural practice, while secondary data were gathered from previous studies on Nias cultural symbols. The analysis revealed that the stone jump, at the denotative level, signifies physical prowess and initiation into adulthood; at the connotative level, it represents courage, social recognition, and masculine pride; and at the mythic level, it embodies the collective identity and resilience of the Nias people amid cultural transformation. The study concludes that, through Barthes’ semiotic lens, Fahombo Batu functions as a living text where traditional values continuously interact with modern interpretations, reflecting the dynamic relationship between heritage, meaning, and contemporary cultural expression.